Secukinumab significantly reduces psoriasis‐related work impairment and indirect costs compared with ustekinumab and etanercept in the United Kingdom. (15th July 2018) - Warren, R.B.; Halliday, A.; Graham, C.N.; Gilloteau, I.; Miles, L.; McBride, D.
Abstract: Background: Psoriasis causes work productivity impairment that increases with disease severity. Whether differential treatment efficacy translates into differential indirect cost savings is unknown. Objective: To assess work hours lost and indirect costs associated with secukinumab versus ustekinumab and etanercept in the United Kingdom (UK). Methods: This was a post hoc analysis of work impairment data collected in the CLEAR study (secukinumab vs. ustekinumab) and applied to the FIXTURE study (secukinumab vs. etanercept). Weighted weekly and annual average indirect costs per patient per treatment were calculated from (i) overall work impairment derived from Work Productivity and Activity Impairment data collected in CLEAR at 16 and 52 weeks by Psoriasis Area and Severity Index (PASI) response level; (ii) weekly/annual work productivity loss by PASI response level; (iii) weekly and annual indirect costs by PASI response level, based on hours of work productivity loss; and (iv) weighted average indirect costs for each treatment. In the primary analysis, work impairment data for employed patients in CLEAR at Week 16 were used to compare secukinumab and ustekinumab. Secondary analyses were conducted at different time points and with patient cohorts, including FIXTURE. Results: In CLEAR, 452 patients (67%) were employed at baseline. At Week 16, percentages of weekly work impairment/mean hours lost decreased with higher PASI: PASI < 50: 22.8%/7.60 h; PASI 50–74: 13.3%/4.45 h; PASI 75–89: 6.4%/2.14 h; PASI ≥ 90: 4.9%/1.65 h. Weighted mean weekly/annual work hours lost were significantly lower for secukinumab than ustekinumab (1.96/102.51 vs. 2.40/125.12; P = 0.0006). Results were consistent for secukinumab versus etanercept (2.29/119.67 vs. 3.59/187.17; Ρ <0.0001). Average annual indirect cost savings with secukinumab were £355 vs. ustekinumab and £1061 versus etanercept. Results at 52 weeks were similar. Conclusions: Secukinumab significantly reduced work impairment and associated indirect costs of psoriasis compared with ustekinumab and etanercept at Week 16 through 52 in the United Kingdom.